2012
DOI: 10.1016/j.toxicon.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous loxoscelism caused by Loxosceles similis venom and neutralization capacity of its specific antivenom

Abstract: Members of the spider genus Loxosceles pose a marked health risk to humans because of the seriousness of the necrotic and systemic effects of their bite, known as loxoscelism. The recent confirmation of Loxosceles similis in residences of Belo Horizonte in Minas Gerais Province, Brazil increases the local potential risk of loxoscelism at higher levels. The first characterization of the venom from this species showed that its main biological effects had a similar intensity as other species (e.g. Loxosceles inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 42 publications
2
4
0
3
Order By: Relevance
“…According to our data, the inflammation increases progressively from two hours and then becomes severe eight hours post L. similis crude venom injection corroborating the already existing studies with L. laeta and L. intermedia venom (15,17,32). Morphometrical parameters showed here can be used to monitor the process dynamics, and also any treatment and sera effectiveness studies (22,31,33,34). In the present study, the heterophils/neutrophils were the predominant cells observed as mentioned by others for loxoscelism.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to our data, the inflammation increases progressively from two hours and then becomes severe eight hours post L. similis crude venom injection corroborating the already existing studies with L. laeta and L. intermedia venom (15,17,32). Morphometrical parameters showed here can be used to monitor the process dynamics, and also any treatment and sera effectiveness studies (22,31,33,34). In the present study, the heterophils/neutrophils were the predominant cells observed as mentioned by others for loxoscelism.…”
Section: Discussionsupporting
confidence: 91%
“…Macroscopically, the radius of the injured area increased over time as previously related in loxoscelism induced by other Loxosceles species (1,6,9). Notably, the venom concentration used in this work was very low (0.5 µg) compared with our previous study of 3 µg of venom, but it was enough to induce a very similar and severe lesion (22). Microscopically, a severe fibrinoushemorrhagic multi-focal acute dermatitis and a necrotic acute myositis were observed.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…[2][3][4][5][6] In almost all cases, supportive care with red blood cell (RBC) transfusions, intravenous fluids, and local wound care are sufficient to provide full recovery. 1,7,8 In more severe cases, hyperbaric oxygen, 9 dapsone, 10,11 and antivenom 12,13 have been used with variable success.…”
mentioning
confidence: 99%
“…Protein quantification was performed in the venom using the Bradford method (Bradford, 1976) with bovine serum albumin (BSA) (Sigma-Aldrich, CA, USA) as the protein standard. The absorbance was measured at 600 nm using an ELx 800 Universal Microplate Reader (Biotek Instruments, VT, USA) according to Chatzaki et al (2012).…”
Section: Methodsmentioning
confidence: 99%